Geminiviruses Associated with the Weed Species Ageratum conyzoides, Centipeda minima, Porophyllum ruderale, and Spilanthes iabadicensis from Java, Indonesia - RIKA MELIANSYAH; SR HENDRASTUTI HIDAYAT; KIKIN HAMZAH MUTAQIN (Indonesian Society for microbiology, 2011)
Geminivirus has a wide host range including cultivated plants and weeds. Infected weeds may play an important role in disease epidemic. Unfortunately, little is known about weeds species that may serve as alternative host for Geminivirus. This research was conducted to identify Geminivirus on weeds around chili pepper field to study their potential role as virus reservoir. Field surveys were conducted to chilli pepper growing area inWest and Central Java Provinces, and The Special Province of Yogyakarta during 2009 to collect symptomatic weed plants. Geminivirus infection was detected using PCR technique from 9 weed samples, i.e. 5 samples Ageratum conyzoides from Bogor (AgrBgr), Sukabumi (AgrSkm), Magelang (AgrMgl), Sleman (AgrJgy), and Garut (AgrGrt); Centipeda minima from Magelang (CtpMgl); A. boehmerioides from Sleman (AcpJgy); Porophyllum ruderale from Bogor (PrlBgr); Spilanthes iabadicensis from Magelang (SplMgl). Further genetic analysis showed that those geminiviruses can be differentiated into 2 clusters, showing the possible genetic differences among them. They neither have a close relationship with other geminiviruses published earlier in the GenBank, indicating weed infecting collected Geminivirus in this study is possibly a distinct Geminivirus.